Christian Education in Colonial and Post-Independent Zimbabwe: A Paradigm Shift - Machingura, Francis (Religions, 2024)
Since the arrival of Christianity in Africa during the pre-colonial era, one of the main characteristics of its spread has been Christian Education (CE). The achievements made thus far by missionaries and African Christian communities were based on the Church-based Christian Education programs that were put into place by churches created by missionaries. Education, let alone Christian Education, has a key role to play in the transformation of every society. The problem is that the type of Christianity and Christian Education introduced sought to uproot Africans from their identity, culture, and language. Christian Education has a crucial role in changing the perspective of citizens to one that is Euro-centric and in promoting effective discipleship and strong doctrinal allegiance among members of mainline churches. Even though Christianity has undergone meaningful change over time, its many manifestations still survive in diverse 21st-century societies. Christianity, just like African Traditional Religion, has permeated every sphere and life of the Zimbabweans. The prospects of Christian Education to foster a positive society’s transformation in Zimbabwe are great and accepted. Two types of Christianity were introduced to Africa: Afro-centric Christianity and Euro-centric Christianity.